Evaluation of microwave-assisted pretreatment of lignocellulosic biomass immersed in alkaline glycerol for fermentable sugars production - Diaz, Ana Belen; Moretti, Marcia Maria de Souza [UNESP]; Bezerra-Bussoli, Carolina [UNESP]; Nunes, Christiane da Costa Carreira [UNESP]; Blandino, Ana; Silva, Roberto da [UNESP]; Gomes, Eleni [UNESP] (Elsevier B.V., 2015)
A pretreatment with microwave irradiation was applied to enhance enzyme hydrolysis of corn straw and rice husk immersed in water, aqueous glycerol or alkaline glycerol. Native and pretreated solids underwent enzyme hydrolysis using the extract obtained from the fermentation of Myceliophthora heterothallica, comparing its efficiency with that of the commercial cellulose cocktail Celluclast (R). The highest saccharification yields, for both corn straw and rice husk, were attained when biomass was pretreated in alkaline glycerol, method that has not been previously reported in literature. Moreover, FTIR, TG and SEM analysis revealed a more significant modification in the structure of corn straw subjected to this pretreatment.Highest global yields were attained with the crude enzyme extract, which might be the result of its content in a great variety of hydrolytic enzymes, as revealed zymogram analysis. Moreover, its hydrolysis efficiency can be improved by its supplementation with commercial beta-glucosidase.
Keywords: Pretreatment; Microwave; Alkaline glycerol; Lignocellulosic biomass; Enzymatic hydrolysis